2012
DOI: 10.1089/vbz.2011.0900
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Tick-Borne Encephalitis in the Czech Republic 1970–2008

Abstract: This article presents major epidemiologic features of tick-borne encephalitis (TBE) in the Czech Republic, using data of laboratory-confirmed cases since 1970. A total of 17,053 cases of TBE were reported in the Czech Republic (population 10 million) in 1970-2008. The data show several important features. First, the pattern of TBE incidence changed over time. Until the end of the 1970s, TBE was characterized by periods of alternately higher and lower incidence (between 180 and 595 cases per year); the 1980s we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 18 publications
0
67
0
4
Order By: Relevance
“…Since we have not defined the term cluster in our questionnaire, we assume that contact points have interpreted this differently. Alimentary infection is well known leading to such clusters and three countries reported such events during the observation period [17][18][19]. The other clusters may also relate to an undiscovered alimentary source or may relate to a natural focus with high prevalence of TBE virus in ticks and a high local transmission (e.g.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Since we have not defined the term cluster in our questionnaire, we assume that contact points have interpreted this differently. Alimentary infection is well known leading to such clusters and three countries reported such events during the observation period [17][18][19]. The other clusters may also relate to an undiscovered alimentary source or may relate to a natural focus with high prevalence of TBE virus in ticks and a high local transmission (e.g.…”
Section: Figurementioning
confidence: 99%
“…In addition, co-feeding of infected and non-infected ticks on the same host as well as trans-stadial and trans-ovarial transmission of the virus, play a major role in virus transmission [13]. While most TBE virus infections of humans occur following the bite of an infected tick, alimentary routes of TBE virus transmis-sion by raw milk consumption have also been described [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the Czech Republic, between 1997 and 2008, there were 7 288 cases of TBEV infection reported, of which 64 (0.9 %) were considered to be food-borne. These were mostly family outbreaks and included the involvement of unpasteurised goat's milk (Kriz et al, 2009). Kerbo et al (2005) reported an outbreak from Estonia in 2005 linked to raw goat's milk.…”
Section: Categorisation Of Hazards Into Main Hazards (Results Of Stepmentioning
confidence: 99%
“…Parez pri tej obliki niso opazili. Ozdravljenje je popolno, brez trajnih posledic (31)(32). Virus prizadene tudi miokard, jetra in druge organe.…”
Section: Klinična Slikaunclassified